How Unexpected Was the 2021 Pacific Northwest Heatwave?. Issue 18 (16th September 2022) - McKinnon, Karen A.; Simpson, Isla R.
Abstract: The 2021 Pacific Northwest heatwave featured record‐smashing high temperatures, raising questions about whether extremes are changing faster than the mean, and challenging our ability to estimate the probability of the event. Here, we identify and draw on the strong relationship between the climatological higher‐order statistics of temperature (skewness and kurtosis) and the magnitude of extreme events to quantify the likelihood of comparable events using a large climate model ensemble (Community Earth System Model version 2 Large Ensemble [CESM2‐LE]). In general, CESM2 can simulate temperature anomalies as extreme as those observed in 2021, but they are rare: temperature anomalies that exceed 4.5 σ occur with an approximate frequency of one in a hundred thousand years. The historical data does not indicate that the upper tail of temperature is warming faster than the mean; however, future projections for locations with similar climatological moments to the Pacific Northwest do show significant positive trends in the probability of the most extreme events. Plain Language Summary: While the 2021 Pacific Northwest heatwave was reasonably well‐forecasted by weather models, it was unexpected by many in the climate community because the high temperatures were so extreme. The event has raised questions about whether the probability of very extreme events is increasing faster than would be expected based on historical warming of average temperatures. Here, we analyze the spread of temperatures around the average, which has increased by 1.5°C since 1960, to provide a rough estimate of the probability of the very extreme event of 2021, and assess whether the probability of extreme heat is changing beyond what is expected from warming of average temperatures. By drawing on climate model simulations from regions that are analogous to the Pacific Northwest, we find that similar events can be simulated by climate models, but that they are very rare: when they occur, they are often the largest event across nearly 10, 000 years of data. The climate model also suggests that the most extreme events may increase in probability in the future beyond what would be expected from the average climate change signal, although we do not yet see clear evidence of this in the observations. Key Points: Summer temperatures in the Pacific Northwest are positively skewed, so hot extremes are more likely than if the distributions were normal Community Earth System Model version 2 (CESM2) can simulate events as extreme as the 2021 Pacific Northwest heatwave at points with similar high‐order statistics, but they are rare Observations do not indicate that the upper tail is warming more than the mean, but CESM2 projects this behavior for very extreme events